The impact of child labour in agricultural sectors in the Vhembe Region : issues and challenges - Masindi, Mphedziseni Moses (University of Limpopo, 2015)
This mini-dissertation deals with the impact of child labour in the Vhembe Region. Africa reportedly has the highest incidence of child labour in the world. Vhembe as a region and South Africa as a whole has the problem of child labour which is influenced by poverty. To respond to this problem, some scholars recommend an outright ban on child labour through legislation. Child labour refers to dangerous and exploitative work which is carried out at too early an age, involves long working hours, carried out in inadequate conditions, not sufficiently paid, involves excessive responsibility, and undermines the child’s dignity and self-esteem. The mini-dissertation has clearly defined the child labour and discusses the legislative framework, international law framework and the challenges of child labour in the Vhembe Region.
Thesis (LLM. (Labour Law)) --University of Limpopo, 2015
Keywords: Child labour; Agricultural sector; Vhembe Region; Child labour - Law and legislation - South Africa; Child labour - South Africa